KETAHANAN PANGAN BERDAMPAK UNTUK SADASARI MENUJU NEW ZERO STUNTING: pencegahan STUNTING - Laila Nurjamilah, Lia; kholiq, abdul; Hendrayana, Yayat (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2026)
Human Resource (HR) development is one of the most important assets in the development of a region, organization, or country. HR refers to individuals or groups who possess the abilities, skills, knowledge, experience, and potential to work and contribute in various sectors. The community service program implemented in Sadasari Village aims to improve food security as part of community self-help efforts to prevent stunting. This program involves active community participation in outreach and various forms of training, with the aim of reducing stunting rates and increasing community knowledge and skills in managing local resources, specifically plant-based food security.